KEPEMIMPINAN SPIRITUAL KEPALA SEKOLAH DALAM PENGUATAN MODERASI BERAGAMA DI SEKOLAH BERBASIS PESANTREN - Elok Ainun Nazilah; Maftuh Maftuh (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to analyze the implementation of spiritual leadership by the principal in strengthening religious moderation at SMP Mambaus Sholihin 7 Bintan, a pesantren-based boarding school in Kepulauan Riau. The school faces a real challenge of student violence cases, indicating a gap between spiritual values and students' daily behavior. This research employs a qualitative descriptive method with a single case study design. Data were collected through passive participatory observation, in-depth interviews with the principal, Islamic education teachers, and students, as well as documentation of curriculum and school policies. Data analysis used the Miles and Huberman interactive model with source, technique, and time triangulation. The study is grounded in Louis W. Fry's spiritual leadership theory (Vision, Hope/Faith, and Altruistic Love) and four religious moderation indicators from the Ministry of Religious Affairs of Indonesia. The findings show that the principal embodies spiritual leadership through a vision-oriented mission culture, personal moral exemplification, faith-based motivation, and altruistic care. These dimensions are manifested through an integrated pesantren curriculum, daily religious habituation programs, anti-bullying policies, and a child-friendly school approach. This study identifies a new mechanism termed the